Pendampingan Pemenuhan Asupan Nutrisi Saat Pandemi COVID-19 Pada Orang Dewasa Perkotaan - Ginna Megawati; Dewi Marhaeni Diah Herawati (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Adults in urban areas were at high risk of infected by a virus caused by COVID-19. This community service aims were to educate the target group's so they can change for better attitudes towards balanced diet recommendations for pandemics time. Using the service-learning method, virtual education has been carried out in the form of audio-visual videos was proven to be able to improve a positive attitude for following balanced diet recommendations.